ANALISIS PERBANDINGAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN COVID-19 DI INDONESIA (Studi Pada Indeks Saham LQ-45 Di Bursa Efek Indonesia) - Aviana Putri Iswanti; Aprilina Susandini (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The Covid-19 case in Indonesia was first announced on March 2, 2020. This study aims to determine whether there is a significant difference in share prices and share trading volume before and after the announcement of Covid-19 in Indonesia on LQ-45 shares on the Indonesia Stock Exchange. . The research data were taken 14 days before and 14 days after the announcement of the first case of Covid-19 in Indonesia. The data analysis was processed with descriptive statistics, the One Sample Kolmogorov-Smirnov Test, and the Wilcoxon Signed Rank Test. From the results of data processing, it shows that there is a significant difference in stock prices before and after the announcement of the first Covid-19 case in Indonesia. This is indicated by a significance value of 0.00 0.05. Where the share price has decreased compared to before the announcement of the Covid-19 case. Meanwhile, the trading volume of shares also shows a significant difference. Where the significance value is 0.00 0.05. The volume of stock trading after the announcement shows an increasing value.